2020
DOI: 10.3389/fpsyg.2020.00244
|View full text |Cite
|
Sign up to set email alerts
|

Causal Structure Learning in Continuous Systems

Abstract: Real causal systems are complicated. Despite this, causal learning research has traditionally emphasized how causal relations can be induced on the basis of idealized events, i.e., those that have been mapped to binary variables and abstracted from time. For example, participants may be asked to assess the efficacy of a headache-relief pill on the basis of multiple patients who take the pill (or not) and find their headache relieved (or not). In contrast, the current study examines learning via interactions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 60 publications
5
27
0
Order By: Relevance
“…In most causal learning paradigms, however, the absence and presence of the cause are explicitly stated and therefore made artificially salient. Another related concern is that many real‐world phenomena are not punctate events that happen at a brief moment in time but instead may persist or fluctuate in intensity over periods and grow or recede in awareness over time (e.g., pain, mood; Davis et al., 2020; Soo & Rottman, 2015. Studying causation with other paradigms over long timeframes will help make the research more realistic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most causal learning paradigms, however, the absence and presence of the cause are explicitly stated and therefore made artificially salient. Another related concern is that many real‐world phenomena are not punctate events that happen at a brief moment in time but instead may persist or fluctuate in intensity over periods and grow or recede in awareness over time (e.g., pain, mood; Davis et al., 2020; Soo & Rottman, 2015. Studying causation with other paradigms over long timeframes will help make the research more realistic.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most major developments in research on causation in the past two decades has been the shift from only focusing how people learn causal strength toward how people learn the causal structure among multiple variables (Bramley, Gerstenberg, Mayrhofer, & Lagnado, 2018;Coenen, Rehder, & Gureckis, 2015;Davis, Bramley, & Rehder, 2020;Rothe, Deverett, Mayrhofer, & Kemp, 2018;Rottman & Keil, 2012;Steyvers, Tenenbaum, Wagenmakers, & Blum, 2003). One reason that this is vitally important is because it helps to distinguish truly causal versus associative representations (though see Fernando (2013) for an associative learning model of causal structure).…”
Section: Causal Strength Versus Causal Structurementioning
confidence: 99%
“…Given limited short-term memory storage and attention, it seems plausible that participants would abstract cues more locally than from the full observation. In other studies, people are found to often use temporally local (i.e., recent) information to drive causal model learning (Bramley, Dayan et al, 2017;Davis et al, 2020). Furthermore, people are often unable to recall older evidence exactly (Bramley et al, 2015;Harman, 1986), rather remembering whatever conclusions they have drawn on the basis of it.…”
Section: Local Evidencementioning
confidence: 98%
“…The literature on contingency learning suggests humans have some ability to condition on other variables when inferring the role of a target variable (Beckers et al, 2005;Gopnik et al, 2001;Rescorla & Wagner, 1972;Shanks, 1985) and, indeed, sensitivity to base rate is one simple form of this. However, recent evidence also demonstrates human limitations in dealing globally with joint probability outside very simple learning problems (Bonawitz et al, 2014;Bramley, Dayan et al, 2017;Davis et al, 2020;Fernbach & Sloman, 2009;Griffiths et al, 2015;Markant et al, 2016). In the causal structure induction setting, complexity quickly compounds in the number of components and events.…”
Section: Local Computationmentioning
confidence: 99%
See 1 more Smart Citation